Antimicrobial Polymers. Issue 12 (19th November 2014) - Jain, Anjali; Duvvuri, L. Sailaja; Farah, Shady; Beyth, Nurit; Domb, Abraham J.; Khan, Wahid
<x xml:space="preserve">Abstract</x> Better health is basic requirement of human being, but the rapid growth of harmful pathogens and their serious health effects pose a significant challenge to modern science. Infections by pathogenic microorganisms are of great concern in many fields such as medical devices, drugs, hospital surfaces/furniture, dental restoration, surgery equipment, health care products, and hygienic applications (e.g., water purification systems, textiles, food packaging and storage, major or domestic appliances etc.) Antimicrobial polymers are the materials having the capability to kill/inhibit the growth of microbes on their surface or surrounding environment. Recently, they gained considerable interest for both academic research and industry and were found to be better than their small molecular counterparts in terms of enhanced efficacy, reduced toxicity, minimized environmental problems, resistance, and prolonged lifetime. Hence, efforts have focused on the development of antimicrobial polymers with all desired characters for optimum activity. In this Review, an overview of different antimicrobial polymers, their mechanism of action, factors affecting antimicrobial activity, and application in various fields are given. Recent advances and the current clinical status of these polymers are also discussed.